Integrated analyses of transcriptome and metabolome provides new insights into the primary and secondary metabolism in response to nitrogen deficiency and soil compaction stress in peanut roots - Yang, Liyu; Wu, Qi; Liang, Haiyan; Yin, Liang; Shen, Pu (Frontiers in Plant Science, 2022)
Peanut (Arachis hypogaea L.) is an important oil crop globally because of its high edible and economic value. However, its yield and quality are often restricted by certain soil factors, especially nitrogen (N) deficiency and soil compaction. To explore the molecular mechanisms and metabolic basis behind the peanut response to N deficiency and soil compaction stresses, transcriptome and metabolome analyses of peanut root were carried out. The results showed that N deficiency and soil compaction stresses clearly impaired the growth and development of peanut’s aboveground and underground parts, as well as its root nodulation. A total of 18645 differentially expressed genes (DEGs) and 875 known differentially accumulated metabolites (DAMs) were identified in peanut root under differing soil compaction and N conditions. The transcriptome analysis revealed that DEGs related to N deficiency were mainly enriched in ‘amino acid metabolism’, ‘starch and sucrose metabolism’ and ‘TCA cycle’ pathways, while DEGs related to soil compaction were mainly enriched in ‘oxidoreductase activity’, ‘lipids metabolism’ and ‘isoflavonoid biosynthesis’ pathways. The metabolome analysis also showed significant differences in the accumulation of metabolisms in these pathways under different stress conditions. Then the involvement of genes and metabolites in pathways of ‘amino acid metabolism’, ‘TCA cycle’, ‘lipids metabolism’, and ‘isoflavonoid biosynthesis’ under different soil compaction and N deficiency stresses were well discussed. This integrated transcriptome and metabolome analysis study enhances our mechanistic knowledge of how peanut plants response to N deficiency and soil compaction stresses. Moreover, its provides new leads to further investigate candidate functional genes and metabolic pathways for use in improving the adaptability of peanut to abiotic stress and accelerating its breeding process of new peanut resistant varieties.